Pendekatan Klinis pada Hepatitis C Kronik - Sherina Aditya; Darmadi Darmadi (Pusat Riset dan Inovasi Nasional, 2026)
Viral hepatitis is a systemic disease that primarily affects the liver and is characterized by a necroinflammatory process that plays a significant role in clinical and laboratory manifestations. Chronic hepatitis is defined as liver inflammation lasting more than six months, with persistent elevations in aminotransferases and characteristic histological features, and carries a risk of progression to cirrhosis and hepatocellular carcinoma. Chronic hepatitis C virus infection occurs due to an ineffective host immune response to the virus, allowing the infection to persist. The innate immune system, particularly type I interferon, plays a key role in the initial defense mechanisms against viral replication. Various antiviral therapies, such as interferon, nucleoside analogs, and nucleotide analogs, are currently available, which have been shown to reduce viral load and inhibit disease progression. Appropriate therapy is expected to prevent long-term complications in patients with chronic hepatitis.